The Effect of Inspiratory Breathing Muscle Exercise Using Respirometer on Changes in Lung Function and Dyspnea Severity in Tuberculosis Pleurisy Patients - Irmaini Irmaini; Herry Priyanto; Dewi Behtri Yanifitri (Jurnal Respirologi Indonesia, 2022)
Background: Respirometer has been commonly used to improve lung function, prevent atelectasis and respiratory complications after surgery. The effectiveness of respirometer to improve lung re-expansion in pleural effusion has not been well studied. So far there is no such study implemented to examine this association in pleural effusion particularly tuberculosis pleurisy in Aceh. Method: This was an experimental pretest-posttest controlled trial in patients with tuberculosis pleurisy hospitalized in dr. Zainoel Abidin Hospital between July and December 2019. Systematic random sampling was used to gather 40 samples, which then divided into intervention and control group consisted of 20 people in each group. All participants performed spirometry and were assessed for dyspnea severity using Borg scale after thoracocentesis and repeated 6 days later. Only intervention group received exercise using respirometer. Data were examined statistically using paired T-test and Mann Whitney Test. Results: The majority of participants were male (68%) with mean age of 42 years old. Around one-third of samples were smokers with mean Brinkman Index of 273 (moderate). The nutritional status was mostly good with mean BMI of 21 (normal). There were significant improvements of FEV1 and FVC values before and after 6 days in both groups. However, if the improvements were compared between intervention and control groups, only FVC improved significantly in intervention group (P= 0.019) whereas FEV1 improved in both groups without significant difference (P= 0.456). Similar result was seen in dyspnea severity where both groups experienced improvement after 6 days with or without intervention. Conclusion: Inspiratory muscle exercise using respirometer could improve lung function, particularly FVC value, significantly and could be an option for additional therapy to help lung re-expansion in tuberculosis pleurisy.